Cultural adaptation and corporate investment decisions: evidence from inter-regional investments - Dan Li; Tusheng Xiao; Chun Yuan (China Journal of Accounting Studies, 2023)
ABSTRACTCorporate inter-regional investment is an important channel for building the domestic economic cycle. This paper explores the impact of firms’ adaptation to regional culture on inter-regional investment based on the sample of newly-established inter-province subsidiaries of A-share listed firms in China from 2006 to 2017. We find that (1) Firms’ low cultural adaptation to home region promote corporate inter-regional investment. (2) Firms are more likely to invest in regions with cultural environments that are more compatible with their own culture value (3) Firms have better investment performance when investing in more culturally adapted regions through better cooperating with new stakeholders and reducing management cost. (4) The impact of cultural adaptation on inter-regional investments is also affected by the state ownership and corresponding regional formal institutions. Our findings have implications for firms to make location choice during inter-regional investment and can help governments attract capital flows.